Mortality from COVID-19 in patients with tuberculosis: systematic review and meta-analysis - I. B. Lebedeva; M. A. Shmakova; O. M. Drozdova; E. B. Brusina (Фундаментальная и клиническая медицина, 2022)
Aim. To perform a systematic analysis of COVID-19 adverse outcomes in patients with tuberculosis.Materials and Methods. We queried PubMed, Cochrane Library, Embase, ClinicalTrials.gov, medRxiv, bioRxiv, and Elibrary databases for studies on COVID-19-related mortality in patients with tuberculosis published from 2020 to 2022. We considered open randomised controlled trials, cohort, and case-control studies. Pseudorandomisation and interventional studies have been excluded from the analysis as well as those without a clear comparison group (i.e., patients without tuberculosis) and duplicate studies.Results. Out of 23,296 hits, 10 studies were included in our review. The risk of death in patients with COVID-19 and tuberculosis was significantly higher (odds ratio = 2.24, 95% confidence interval = 1.46 – 3.43] as compared with the patients without tuberculosis.Conclusion. Tuberculosis is associated with COVID-19-related mortality.